Chatgpt utilization for efficient test question design: A case study at smk hisba buana semarang - Aliwan; Moh Fasin Fahsin; Abdul Latif Zen Latif; Abdul Hakim Hakim; Moch Choirudin; Zaid Barzenji (Yayasan Azhar Amanaa Yogyakarta, 2025)
The development of artificial intelligence (AI) such as ChatGPT, is increasingly being used in the field of education, especially in the preparation of written exam questions. This study focuses on teachers at SMK Hisba Buana Semarang in utilizing ChatGPT to create written exam questions, with the aim of examining the benefits obtained, obstacles faced, and solutions that can be applied. This study was conducted using qualitative methods through interviews, observations, and document analysis, which were then processed descriptively. The results of this study are (1) Utilization of ChatGPT for teachers at SMK Hisba Buana Semarang has used ChatGPT to assist in the preparation of written test questions. The use of ChatGPT has been proven to be able to produce various types of questions, including multiple choice, essays, which are in accordance with the evaluation needs at the school. Teachers can give orders to ChatGPT to produce questions with different levels of difficulty according to the expected competencies (2) There are advantages, namely time efficiency, question variations, flexibility, increased creativity, accessibility. Some disadvantages are the accuracy of the questions, lack of specific context, no question validation, possibility of bias, technology dependence. There are several obstacles and solutions, namely training for teachers on how to use ChatGPT effectively in compiling questions, Teachers need to provide more specific input so that the questions produced are in accordance with the applicable curriculum, The questions produced need to go through a revision and validation stage before being used in the exam, Teachers must review and edit questions to ensure originality, Schools can provide facilities or alternative devices that allow the use of this technology without obstacles. In conclusion, ChatGPT can be an effective tool in the process of creating written questions, as long as it is used wisely and combined with teacher creativity, and supported by good training and adequate infrastructure.